On the path to aqueous organic redox flow batteries: Alizarin red S alkaline negolyte. Performance evaluation and photochemical studies - Alan Lima (2021)
An aqueous organic redox flow battery (AORFB) based on Alizarin Red S, 3,4-dihydroxy-9,10-anthraquinone-2-sulfonic acid (ARS) and potassium ferrocyanide (PF) was studied in alkaline medium. Charge-discharge processes and potential-current response behaviour in a full cell combining ARS, as the negolyte, and PF, as the posolyte, were investigated. The diffusion coefficient (D) and kinetic rate constant (k0) of ARS were obtained from electrochemical measurements indicating a two-electron reduction reaction of ARS. The electrochemical stability test of the redox pair showed that the negolyte (ARS), even when subjected to extreme potential and current conditions, does not lose its redox activity and exhibits good performance without significant losses of efficiencies in a single cell test. The AORFB was found stable with an average storage capacity of 5.9 mWh L-1 and capacity retention of 89 and 91.5% for a single cell test before and after stability test, respectively. Additionally, the photophysics of ARS was investigated aiming to rationalize the stability of the compound as negolyte. The system showed to have potential as an organic aqueous flow battery closely related to the electrochemical stability and efficiencies associated to ARS.